Membrane interactions and self‐association of components of the Ess/Type VII secretion system of Staphylococcus aureus. Issue 3 (3rd February 2016) - Jäger, Franziska; Zoltner, Martin; Kneuper, Holger; Hunter, William N.; Palmer, Tracy
Abstract : The Ess/Type VII protein secretion system, essential for virulence of pathogenic Staphylococcus aureus, is dependent upon the four core membrane proteins EssA, EssB, EssC and EsaA. Here, we use crosslinking and blue native PAGE analysis to show that the EssB, EssC and EsaA proteins individually form homomeric complexes. Surprisingly, these components appear unable to interact with each other, or with the EssA protein. We further show that two high molecular weight multimers of EssC detected in whole cells are not dependent upon the presence of EsxA, EsxB or any other Ess component for their assembly. Abstract :